Assessing Quality of Healthcare Delivery When Making Choices: National Survey on Health Consumers' Decision Making Practices - Mark Avery; Allan Cripps; Gary D Rogers (ACHSM, 2021)
Objective: Choices and quality decisions made by consumers in relation to their healthcare have been associated with personal experience of those services, interpersonal engagement and reliance on third-party information, as well as the subsequent satisfaction with the service. The purpose of this research was to understand current information sources, determinants of quality discernment and decision-making factors by consumers in the Australian community in relation to healthcare. Method:  Conventional content analysis research was undertaken in the form of a national telephone survey of 200 consumers. Open-ended questions were used to elicit information from the general community. Results: Reputation and other key interpersonal and structural elements are utilised in determining quality of healthcare services as well as in deployment as key factors in decision-making regarding use of healthcare services. While most respondents valued and used key information about provider relationships, outcomes performance and performance rankings, up to 20% of respondents did not know or could not identify ways in which they would assess and evaluate the quality of healthcare services. Conclusion: This research identifies that consumers use a range of information and advice relating to experience, interpersonal engagement and information from third-party sources. If healthcare providers develop clearer communications around their technical, procedural and conduct principles, consumers will be in a better position to evaluate reputation and make decisions about their healthcare needs and the health system.